Modal Analysis Of High Frequency Acoustic Signal Approach For Progressive Failure Monitoring In Thin Composite Plates - Z. M., Hafizi; Epaarachchi, J.; Lau, K. T. (2012)

(untitled)
During the past few decades, many successful research works have evidently shown remarkable capability of Acoustic Emission (AE) for early damage detection of composite materials. Modal Analysis of AE signals or Modal Acoustic Emission (MAE) offers a better theoretical background for acoustic emission analysis which is necessary to get more qualitative and quantitative result. In this paper, the application of MAE concept in a single channel AE source location detection method for failure characterization and monitoring in thin composite plates was presented. Single channel AE source location is one of the recent studies for composite early damage localization, owing to the growing interest and knowledge of modal analysis of AE wave. A tensile test was conducted for glass fiber epoxy resin specimen with small notch. A single channel of AE system was used to determine the AE source location on specimen under testing. The results revealed that AE single channel source location provides reasonable accuracy for glass fiber laminate which was tested.